Screening performance of C-reactive protein for active pulmonary tuberculosis in HIV-positive patients: A systematic review with a meta-analysis - Meca, Andreea-Daniela; Turcu-Stiolica, Adina; Bogdan, Maria; Subtirelu, Mihaela-Simona; Cocoș, Relu; Ungureanu, Bogdan Silviu; Mahler, Beatrice; Pisoschi, Catalina-Gabriela (Frontiers in Immunology, 2022)
Background: Tuberculosis (TB) is the leading infectious cause of mortality worldwide. In the last years, resistant strains of the etiological agent, Mycobacterium tuberculosis, have emerged, thus demanding more triage tests to identify active pulmonary TB (PTB) patients and to evaluate their disease severity. Therefore, acute-phase reaction serum tests are required for monitoring TB patients, among WHO symptoms screening recommendations. C-reactive protein (CRP) is a non-specific inflammatory biomarker that has been recently proposed for TB screening and can be quantitatively analyzed through cost-effective point-of-care assays. A previous meta-analysis found CRP highly sensitive and moderate specific for active PTB with confirmed HIV infection. Methods: We performed an update meta-analysis of diagnostic tests, pooling sensitivities and specificities in order to assess the accuracy of CRP as a potential test for the screening of HIV-associated PTB in outpatients. We searched MEDLINE, Web of Science, and SCOPUS, for eligible articles before October 19th, 2021. Results: We identified 13 eligible studies with HIV-positive patients with PTB. At CRP threshold of 10mg/L, CRP pooled sensitivity was 87% (76%-93%) and pooled specificity was 67% (49%-81%), with Area under the Curve (AUC) of 0.858. Using CRP threshold of 8mg/L, pooled sensitivity was 82% (72%-89%) and pooled specificity was 82% (67%-92%), with AUC of 0.879. We found that CRP has a high sensitivity in screening of PTB in HIV-positive outpatients, consistent with findings reported previously. Conclusions: Regardless of pooled specificity, better results were found using the CRP threshold of 8mg/L as a test screening of PTB, meeting the need of further approaching specific TB diagnostic methods and reducing resource consumption.